Development of a Novel Assay Based on Plant-Produced Infectious Bursal Disease Virus VP3 for the Differentiation of Infected From Vaccinated Animals - Bortolami, Alessio; Donini, Marcello; Marusic, Carla; Lico, Chiara; Drissi Touzani, Charifa; Gobbo, Federica; Mazzacan, Elisa; Fortin, Andrea; Panzarin, Valentina Maria; Bonfante, Francesco; Baschieri, Selene; Terregino, Calogero (Frontiers in Plant Science, 2021)
Infectious bursal disease virus (IBDV) is the causative agent of Gumboro disease, a severe infection that affects young chickens and is associated with lymphoid depletion in the bursa of Fabricius. Traditional containment strategies are based either on inactivated or live-attenuated vaccines. These approaches have several limitations such as residual virulence or low efficacy in the presence of Maternally Derived Antibodies (MDA) but, most importantly, the impossibility to detect the occurrence of natural infections in vaccinated flocks. Therefore, the development of novel vaccination strategies allowing the Differentiation of Infected from Vaccinated Animals (DIVA) is a priority. Recently, commercial vectored and experimental subunit vaccines based on VP2 have been proved effective in protecting from clinical disease and posed the bases for the development of novel DIVA strategies. In this work an engineered version of the VP3 protein of IBDV (His-VP3) was produced in plants, successfully purified from Nicotiana benthamiana leaves and used to develop an enzyme-linked immunosorbent assay (ELISA) for the detection of anti-VP3 antibodies. The His-VP3 ELISA was validated with a panel of 180 reference sera and demonstrated to have 100% sensitivity (95% Confidence interval – CI: 94.7 - 100.0) and 94.17% specificity (95% CI: 88.4 – 97.6). To evaluate the application of His-VP3 ELISA as a DIVA test, the novel assay was used to monitor, in combination with a commercial kit detecting anti-VP2 antibodies, the immune response of chickens previously immunized with an inactivated IBDV vaccine, a recombinant Turkey herpesvirus carrying the VP2 of IBDV (HVT-ND-IBD) or with plant-produced VP2 particles. The combined tests correctly identified the immune status of the vaccinated Specific Pathogen Free White-leghorn chickens. Moreover, the His-VP3 ELISA correctly detected MDA against VP3 in commercial broiler chicks and showed that antibody titers fade with time, consistent with the natural decrease of maternally derived immunity. Finally, the novel assay, in combination with a VP2-specific ELISA, demonstrated its potential application as DIVA test in chickens inoculated with VP2-based vaccines, being able to detect the seroconversion after challenge with a very virulent IBDV strain.